Karakteristik Edible Film Gelatin-Kitosan dengan Tambahan Ekstrak Genjer (Limnocharis flava) dan Aplikasi pada Pempek - Haidir Ali; Ace Baehaki; Shanti Dwita Lestari (Jurnal FishtecH, 2017)
The purpose of this research was to observed the effects of yellow velvetleaf fruit estrats on the characteristics fruit extracts on the characteristics of gelatin-chitosan edible film and its application in pempek. The ability of film to inhibit the spoilage of pempek was also studied. This research used a Randomized Block Design (RBD) in the first stage and Design Randomized Factorial (DRF) in the second stage with two-factor and two repetitions. Factors treatment consists of velvetleaf extract concentrations (0, 10, 20%) and the storage time (0, 1, 2 days). The first phase edible film was characterized basedon solubility, thickness, water vapor transmission and the percent extension, the second phase while their ability to protect pempek produk were assessed though the changes on water content, total volatile base-N (TVB-B), total plate count (TPC) yeasts and molds of the products during storage 2 days. The results of the first phase of research showed the addition of extract yellow velvetleaf no significant effect on the solubility, thickness and water vapor transmission while give the significant effect on the percent extension. The results of the second phase research showed the interaction between the addition of yellow velvetleaf extract and storage time significant effect on water content, total plate count (TPC) and yeast fungi while the total volatile base-N (TVB-N) effect is no significant effect. The best treatment of the first study, was A1 (Extra yellow velvetleaf 10%). Activity antimicrobe, Solubility, thickness, water vapor transmission and the percent extension of each is 3.75mm, 98.14%, 0.18 mm, 7.40 g/m2.24jam, 63.66%. The best treatment of the second study is A1B1 (extract yellow velvetleaf 0% and first day of storage time). Water content, total volatile base-N (TVB-N), total plate count (TPC) yeasts and molds, respectively 54.68%, 9.3 mg/100 g, 7.22x103 CFU/g, and 5.32x104 CFU/g.